Effects of Humic Substances on Cotton (Gossypium hirsutum L.) - Temiz, Mefhar; Karahan, Ender; Kenan Koca, Yakup (Asian Journal of Chemistry, 2010)
Soil organic matter is a fundamental, but dynamic component of soils that influences many chemical, physical and biological properties that regulate soil productivity. An important objective for using humic substances in cotton is to balance vegetative and reproductive growth as well as to improve lint yield and fiber quality. Field study was conducted in a randomized complete block design with 3 replications under irrigated conditions at Diyarbakir in 2004, to determine the effects of different humic acid treatments (seed soaking, foliar spray, seed soaking + foliar spray) on yield and fiber technological properties of cotton. The comparison with the untreated control, application of humic acid significantly affected fiber length, fiber uniformity (variety × treatment interaction) and micronaire (treatment) parameters, whereas there were no significant differences in lint turnout, seed-cotton yield and fiber strength parametres.